2023
DOI: 10.3892/br.2023.1620
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Gastrodia elata Blume in a Caenorhabditis elegans model of Alzheimer's disease based on network pharmacology

Abstract: The aim of the present study was to investigate the protective effect of Gastrodia elata Blume (GEB) against Caenorhabditis elegans ( C. elegans ) in Alzheimer's disease (AD) through network pharmacology. Firstly, the active constituents of GEB through ETCM and BATMAN-TCM databases were collected and its potential AD-related targets in Swiss Target Prediction were predicted. The potential targets related to AD were collected from the GeneCard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Previous reports have indicated that treatment with PCA was helpful for nematodes against heat stress, osmotic stress, and oxidative stress ( Kim et al, 2014 ; Schmitt et al, 2021 ). In addition, treatment with PAL could delay paralysis and inhibit aggregation of Aβ plaques, suggesting its neuroprotective effect ( Shi et al, 2023 ). We found that treatment with both 10–100 μM PCA and 10–100 μM PAL inhibited adverse effect of SC5314 infection in decreasing lifespan ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have indicated that treatment with PCA was helpful for nematodes against heat stress, osmotic stress, and oxidative stress ( Kim et al, 2014 ; Schmitt et al, 2021 ). In addition, treatment with PAL could delay paralysis and inhibit aggregation of Aβ plaques, suggesting its neuroprotective effect ( Shi et al, 2023 ). We found that treatment with both 10–100 μM PCA and 10–100 μM PAL inhibited adverse effect of SC5314 infection in decreasing lifespan ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…G. elata is a very important medicinal orchid with documented therapeutic properties [3][4][5][7][8][9][10]. It is, therefore, essential to improve its production.…”
Section: Discussionmentioning
confidence: 99%
“…[3,6]. Pharmacological studies have shown that the plant has a neuroprotective ability and may represent an essential resource for the treatment of chronic diseases, including Alzheimer's, epilepsy, dementia, brain aging-related diseases, hypertension, depression, and for the improvement of blood flow in the brain and heart [7][8][9][10][11]. Accordingly, the demand for high-quality G. elata is increasing, and the reliance on wild G. elata from mountainous regions is leading to its scarcity and an inability to meet market demand [6,11].…”
Section: Introductionmentioning
confidence: 99%
“…Gastrodia elata is a well-known and valuable medicinal herb with a distinctive odor that is suitable for growing in moist and well-ventilated shady environments, such as Yunnan and Guizhou in China. Studies have shown that Gastrodia elata and its extracts have potential for use in the prevention and treatment of AD ( Shi et al, 2023a ). Indeed, one of the active ingredients of Gastrodia elata , p-hydroxybenzyl alcohol, was reported to ameliorate Aβ-induced toxic effects ( Liu et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%